2014
DOI: 10.1021/jp504922e
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic and Kinetic Analyses of the CO2 Chemisorption Mechanism on Na2TiO3: Experimental and Theoretical Evidences

Abstract: Sodium metatitanate (Na2TiO3) was successfully synthesized via a solid-state reaction. The Na2TiO3 structure and microstructure were characterized using X-ray diffraction, scanning and transmission electron microscopy, and N2 adsorption. Then, the CO2 chemisorption mechanism on Na2TiO3 was systematically analyzed to determine the influence of temperature. The CO2 chemisorption capacity of Na2TiO3 was evaluated both dynamically and isothermally, and the products were reanalyzed to elucidate the Na2TiO3–CO2 reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 96 publications
5
27
0
Order By: Relevance
“…In addition, these k and DH à values are not substantially different from those reported for other sodium ceramics [18,20,47,48]. For example, the reported k values for Na 2 ZrO 3 are between 1 Â 10 À3 and 2 Â 10 À2 s À1 at the optimum CO 2 capture temperatures (i.e., 600-700°C) with a DH à value of 33 kJ/mol [18,20], and Na 2 TiO 3 exhibited a k values of 1.7-2.5 Â 10 À4 s À1 and a DH à value of 140.9 kJ/mol under the best capture conditions (i.e., 600 and 650°C) [49]. Therefore, these results clearly indicate that CO 2 chemisorption on Na 0.89 CoO 1.95 was slower than that on Na 2 ZrO 3 but considerably faster than that on Na 2 TiO 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these k and DH à values are not substantially different from those reported for other sodium ceramics [18,20,47,48]. For example, the reported k values for Na 2 ZrO 3 are between 1 Â 10 À3 and 2 Â 10 À2 s À1 at the optimum CO 2 capture temperatures (i.e., 600-700°C) with a DH à value of 33 kJ/mol [18,20], and Na 2 TiO 3 exhibited a k values of 1.7-2.5 Â 10 À4 s À1 and a DH à value of 140.9 kJ/mol under the best capture conditions (i.e., 600 and 650°C) [49]. Therefore, these results clearly indicate that CO 2 chemisorption on Na 0.89 CoO 1.95 was slower than that on Na 2 ZrO 3 but considerably faster than that on Na 2 TiO 3 .…”
Section: Resultsmentioning
confidence: 99%
“…To further analyze the isothermal curves shown in Fig. 4, these data were fitted to a first-order reaction [14,18,49]. This model was selected because there are several processes involved in this reaction mechanism, such as different CO 2 chemisorption processes (superficial and bulk chemisorptions) and cobalt reduction processes.…”
Section: Resultsmentioning
confidence: 99%
“…Fitting the experimental data to the double exponential model showed that the lithium diffusion process was the limiting step of the whole CO 2 sorption process. This [164,169,175] have published several papers about the application of the rate law model for analyzing the mechanism of CO 2 adsorption on different ceramics such as Li 8 SiO 6 , Na 2 TiO 3 , and Na 2 ZrO 3 . The rate law model is used when several processes are involved in the mechanism of CO 2 adsorption.…”
Section: Kinetic Modelsmentioning
confidence: 99%
“…The AvramieErofeev model was found to be most suitable for analyzing the kinetic behavior of both sorption and desorption process, and effect of water. Heriberto Pfeiffer and co-workers have published many papers on systematic thermokinetic analyses of other ceramics including Na 2 ZrO 3 , Li 5 AlO 4 , Li 8 SiO 6 , Na 2 TiO 3 and Na 2 SiO 3 (Duran-Munoz et al, 2013;AvalosRendon et al, 2009;Sanchez-Camacho et al, 2014;AlcerrecaCorte et al, 2008;Rodriguez and Pfeiffer, 2008). Now, it has been accepted that the CO 2 capture in all these ceramics occurs through a chemisorption process.…”
Section: Reaction Mechanism and Kinetic Behaviors Of Ceramicsmentioning
confidence: 99%
“…There are only two reports about the use of Na 2 TiO 3 as a possible CO 2 captor (Sanchez-Camacho et al, 2014;L opez-Ortiz et al, 2010). Sanchez-Camacho et al (2014) systematically analyzed the influence of temperature on CO 2 chemisorption by Na 2 TiO 3 .…”
Section: Sodium Metatitanate (Na 2 Tio 3 )mentioning
confidence: 99%